2021
DOI: 10.3389/fitd.2021.747820
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania infantum Infection Modulates the Jak-STAT Pathway in Lutzomyia longipalpis LL5 Embryonic Cells and Adult Females, and Affects Parasite Growth in the Sand Fly

Abstract: Phlebotomine sand flies (Diptera, Psychodidae) belonging to the Lutzomyia genus transmit zoonoses in the New World. Lutzomyia longipalpis is the main vector of Leishmania infantum, which is the causative agent of visceral leishmaniasis in Brazil. To identify key molecular aspects involved in the interaction between vector and pathogens and contribute to developing disease transmission controls, we investigated the sand fly innate immunity mediated by the Janus kinase/signal transducer and activator of transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…We observed that the expression of PpRel gene was similar in both guts and carcasses samples, indicating that the IMD pathway can be regulated across P. papatasi body. Our results showed a significant reduction of PpAtt and PpDef2 genes in the carcasses when PpRel was silenced with 150 ng of dsRNA, a commonly used amount of dsRNA in sand flies (Sant'Anna et al, 2008;Sant'Anna et al, 2009;Diaz-Albiter et al, 2011;Telleria et al, 2012;Telleria et al, 2021b;Telleria et al, 2021a;Di-Blasi et al, 2019). Nevertheless, PpRel silencing was not significantly reached in the guts with this same amount of dsRel.…”
Section: Discussionmentioning
confidence: 64%
“…We observed that the expression of PpRel gene was similar in both guts and carcasses samples, indicating that the IMD pathway can be regulated across P. papatasi body. Our results showed a significant reduction of PpAtt and PpDef2 genes in the carcasses when PpRel was silenced with 150 ng of dsRNA, a commonly used amount of dsRNA in sand flies (Sant'Anna et al, 2008;Sant'Anna et al, 2009;Diaz-Albiter et al, 2011;Telleria et al, 2012;Telleria et al, 2021b;Telleria et al, 2021a;Di-Blasi et al, 2019). Nevertheless, PpRel silencing was not significantly reached in the guts with this same amount of dsRel.…”
Section: Discussionmentioning
confidence: 64%
“…At least three independent experiments were performed. Primer sequences used for A. aegypti, A. aquasalis, L. longipalpis and R. prolixus experiments are listed in Table S1 and in Barletta and collaborators (4); Bahia and collaborators (8, 10); Telleria and collaborators (16,39), Tinoco-Nunes and colleagues ( 14); Berni and collaborators ( 40) Majerowicz and colleagues (36), Vieira and collaborators (41). The 16S rRNA gene was used to quantify bacterial community abundance (42).…”
Section: Rna Extraction Cdna Synthesis and Qpcr Analysismentioning
confidence: 99%
“…We have previously shown irrefutably that L. longipalpis presents immune responses to Leishmania infections. In the case of sand flies infected by L. ( L. ) infantum , the suppression of the Jak-STAT [ 48 ] or activation of IMD pathways [ 49 ] affected the survival of the parasite in the vector, and TGF-beta also had a role in the success of the infection [ 50 ]. We already showed that exosomes secreted by parasites from logarithmic and stationary phase cultures, equivalent to the insect forms, carry a plethora of Leishmania virulence factors [ 46 ].…”
Section: Discussionmentioning
confidence: 99%